The Armament and Equipment of the Members of the Court Banner of the Kings of Poland in the second half of the 15th century - Kałużny, Jędrzej Tomasz (Tools of War, 2023)
The court banner of the Polish kings was composed of mounted knights (curieses) and maids (cubicularii), at the head of mounted troops of various sizes. Archival materials from the Central Archives of Historical Records in Warsaw contain information from the second half of the 15th century about 11 500 cavalrymen serving in the court unit. The author characterized various types of sources informing about the court banner – riders, equipment and horses. Due to the armament, the riders can be divided into heavily armed – in lance armor (zbroja kopijnicza), medium-armed - in shooter’s armor (zbroja strzelcza), and lightly armed - armed in the Rascian (in Old Polish equivalent Serb) or Tatar style. The author also discusses individual types of offensive and protective weapons used by horsemen from the court unit. The article also analyzed information about horses, their breeds, varieties, wages and health. As the author notes, in terms of weapons, the equipment of courtiers did not differ from that used by mercenaries or common knights. It is worth noting that the oldest mentions of firearms used by horse riders in Poland concern courtiers who were carrying rifles as early as 1497.